Relationship between hydraulic anisotropy and soil properties - Su, Jeremy Xiong Chang (2015)
Many geotechnical and soil engineering applications today deal with unsaturated soil, which does not follow the principles of classical soil mechanics. Of particular concern is the soil permeability, which is the most variable property and most difficult to predict. Furthermore, unsaturated soil permeability often varies with the direction of water flow, causing the soil to exhibit hydraulic anisotropy. The nature and variability of hydraulic anisotropy in a homogenous soil is not well known. Hence, this study aims to explore and better understand the hydraulic anisotropy of the soil in the saturated and unsaturated conditions. In order to make hydraulic anisotropy more pronounced in this study, the soil used in this Project included flakes of coarse mica to increase parallelism of soil particle arrangement in the horizontal direction. Past research has also indicated that the presence of mica significantly affects the shear and strength anisotropy of soil, and hence mica was included in the soil tested to gauge the effect of mica on hydraulic anisotropy. Soil specimens were tested for their saturated permeability and their Soil-Water Characteristic Curves (SWCC) across two drying and wetting cycles using triaxial tests. The SWCC curves between 2 specimens layered vertically and horizontally were shown to be almost identical, and an almost constant difference in permeability was observed across the matric suctions tested, indicating a consistent hydraulic anisotropy throughout the saturated and unsaturated conditions.